Revitalization of Ijarah Agreements in Islamic Banking Service Products - Khulwah, Juhrotul (Sahabat Publikasi, 2024)
The revitalization of the ijarah contract is urgently needed by the community so that the community not only uses the classic ijarah contract in daily life but can use the ijarah contract that has been revitalized in modern times, such as the muntahiyah bi al-tamlik ijarah contract and multi-service ijarah contract, so that more service products can be produced from the ijarah contract, and can make the community more empowered by the continuous development of the times. This study aims to explain ijarah contracts that have undergone revitalization so that they can be used more by the community, to develop the service products used. So the problem in this study is